2018
DOI: 10.1002/stem.2746
|View full text |Cite
|
Sign up to set email alerts
|

Low Osteogenic Yield in Human Pluripotent Stem Cells Associates with Differential Neural Crest Promoter Methylation

Abstract: SUMMARY Human pluripotent stem cell-derived osteoblasts possess great potential for utilization in bone disorder elucidation and repair; yet, while the general ability of human pluripotent stem cells to differentiate into osteoblasts and lay down bone-specific matrix has been shown, previous studies lack the complete characterization of the process whereby such osteoblasts are derived as well as a comparison between the osteogenic efficiency of multiple cell lines. Here, we compared the osteogenic potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 75 publications
(91 reference statements)
0
30
0
Order By: Relevance
“…However, a powerful alternative has emerged through modeling human NC development using human embryonic stem cells (hESCs) (Pomp et al, 2005). Initial efforts relied on co-cultures, the use of serum or serum-replacement cocktails, and either embryoid bodies or neural rosettes (Bajpai et al, 2010;Brokhman et al, 2008;Curchoe et al, 2010;Jiang et al, 2009;Lee et al, 2007;Liu et al, 2012;Rada-Iglesias et al, 2012;Sparks et al, 2018). Simpler models, where cell density was controlled along with defined media components, have enabled a better analysis of contributing factors during human NC development from hESCs (Fukuta et al, 2014;Hackland et al, 2017;Huang et al, 2016;Leung et al, 2016;Menendez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, a powerful alternative has emerged through modeling human NC development using human embryonic stem cells (hESCs) (Pomp et al, 2005). Initial efforts relied on co-cultures, the use of serum or serum-replacement cocktails, and either embryoid bodies or neural rosettes (Bajpai et al, 2010;Brokhman et al, 2008;Curchoe et al, 2010;Jiang et al, 2009;Lee et al, 2007;Liu et al, 2012;Rada-Iglesias et al, 2012;Sparks et al, 2018). Simpler models, where cell density was controlled along with defined media components, have enabled a better analysis of contributing factors during human NC development from hESCs (Fukuta et al, 2014;Hackland et al, 2017;Huang et al, 2016;Leung et al, 2016;Menendez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have also demonstrated the potential of hPSC to phenocopy osteogenic defects associated with genetic disorders such as progressive fibrodysplasia ossificans or Marfan syndrome [39,40]. Nonetheless, these different applications of hPSCs are hindered by the differentiation inconsistency of individual hPSC lines and the fact that the molecular mechanism underlying the interline variability has remained elusive [41]. Based on the analysis of a dozen hPSC lines that replicated the observed variability in osteogenic capacity, we demonstrated that a reduced expression of miRNAs belonging to the imprinted DLK1/DIO3 locus was associated with a low osteogenic yield of hPSC lines.…”
Section: Discussionmentioning
confidence: 99%
“…H9 human embryonic stem cells (hESCs) were obtained from WiCell and were cultured on Matrigel (BD Biosciences) treated culture plates in mTeSR 1 medium (Stem Cell Technologies) as feeder-free cultures at 37°C with 5% CO 2 as described [32]. Colonies were passaged every 5 days using accutase treatment (2-4 min at room temperature) and a cell scraper to dislodge cell clumps from the plastic.…”
Section: Cell Culturementioning
confidence: 99%
“…This process of calcification is facilitated by the osteoblast, which secretes a collagenous matrix as the frame work for the hydroxyapatite formation as well as all other extracellular matrix (ECM) proteins necessary for bone function [26]. Among these, osteocalcin (OCN) is uniquely found only in bone tissue, which is why its presence is often used as a biomarker for osteogenesis [27][28][29][30][31][32]. The ability of osteoblasts to calcify the ECM can also be confirmed by calcium specific stains, such as von Kossa or Alizarin Red [28,30,[32][33][34], but this type of assessment is often qualitative.…”
Section: Introductionmentioning
confidence: 99%